Optimal agricultural water allocation for enhanced productivity of hot pepper (Capsicum annum L) and economic gain: an experimental study from Southern Ethiopia - Gezimu Gelu; Chanako Dane; Alemnesh Ayza; Markos Habtewold (Cogent Food & Agriculture)
The experiment was conducted to determine the irrigation scheduling effect on hot pepper green pods, yield attributes, and irrigation water productivity (WP) in the Arba Minch area. Field trials comprised five levels of treatments: 140 % MAD, 120% MAD, 100% MAD, 80% MAD and 60% MAD. The results revealed that different depletion levels had significantly affected hot pepper’s yield and related attributes. The maximum yield of hot pepper was observed under 100% MAD without significant variation of 120% MAD whereas the minimum was under 140% MAD in both years of experimentation. WP was also highly influenced by depletion, and the maximum water productivity of (24.67 kg/ha-mm, 24.72 kg/ha-mm was observed under 120% MAD and minimum (19.26 kg/ha-mm, 16.49 kg/ha-mm) under 60% MAD in the year 2019 and 2021, respectively. The results revealed that as the level of depletion increased, irrigation frequency (event) increased, yield and water productivity decreased of hot peppers. 120% MAD offered the highest economic return (11,795.96 US$) and saved water, wage, and irrigation events compared to more frequent applications. The current findings showed that applying 120% MAD is better for hot pepper production in the Arba Minch areas and similar ecology.